2016
DOI: 10.1016/j.celrep.2016.01.063
|View full text |Cite
|
Sign up to set email alerts
|

Condensin Smc2-Smc4 Dimers Are Flexible and Dynamic

Abstract: SummaryStructural maintenance of chromosomes (SMC) protein complexes, including cohesin and condensin, play key roles in the regulation of higher-order chromosome organization. Even though SMC proteins are thought to mechanistically determine the function of the complexes, their native conformations and dynamics have remained unclear. Here, we probe the topology of Smc2-Smc4 dimers of the S. cerevisiae condensin complex with high-speed atomic force microscopy (AFM) in liquid. We show that the Smc2-Smc4 coiled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
70
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(86 citation statements)
references
References 29 publications
15
70
0
Order By: Relevance
“…Indeed, almost universal evidence from EM, FRET, chemical cross-linking, and atomic force microscopy (AFM) documents rodlike condensin complexes [22,37,38,42,43]. A notable exception comes from liquid AFM performed on in vivo–assembled but extracted and purified yeast condensins [44]. In that study, condensins were predominantly folded over to promote hinge–head associations, but rings and lassos (dissociated heads in which only one appeared bound to the hinge) were also observed.…”
Section: Cohesins: Rod or Ring?mentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, almost universal evidence from EM, FRET, chemical cross-linking, and atomic force microscopy (AFM) documents rodlike condensin complexes [22,37,38,42,43]. A notable exception comes from liquid AFM performed on in vivo–assembled but extracted and purified yeast condensins [44]. In that study, condensins were predominantly folded over to promote hinge–head associations, but rings and lassos (dissociated heads in which only one appeared bound to the hinge) were also observed.…”
Section: Cohesins: Rod or Ring?mentioning
confidence: 99%
“…In that study, condensins were predominantly folded over to promote hinge–head associations, but rings and lassos (dissociated heads in which only one appeared bound to the hinge) were also observed. Whether such intermediate structures are predicated on the dynamics of partially disrupted and flexible complexes (having survived extractions and enrichments) or represent functional cycles (despite conformation changes that occur in the absence of DNA and ATP) remains unknown [44]. Regardless, the similar degree of conservation among coiled coil domains within Smc1,3 cohesin, and Smc2,4 condensin family members is consistent with the notion that mutation is limited or constrained to preserve intermolecular binding along the entire coiled coil domain [45,46].…”
Section: Cohesins: Rod or Ring?mentioning
confidence: 99%
See 1 more Smart Citation
“…3E). It is reported that condensin is very flexible (Eeftens et al 2016) (short persistence length, 4 nm), and thus may show bursts of directed motion in vivo, depending on the distribution of tethers along the chromosome.…”
Section: Resultsmentioning
confidence: 99%
“…There are 11 beads in the condensin holocomplex; each bead is ∼10 nm in diameter. Condensin is a very flexible molecule, showing a persistence length of ∼4 nm (Eeftens et al 2016), about one-tenth that of DNA (50 nm). The chains of the antiparallel coiled-coils fold back on one another to length of 45 nm.…”
Section: Model Assumptionsmentioning
confidence: 99%